The Significance of Memory in the Teaching/Learning Process: (Techniques for Improving Memory) - Shmavonyan, Gayane; Karapetyan, Lili (Armenian Folia Anglistika, 2011)
The role of memory as part of a person’s mental activity has long been recognized by psychologists, methodologists and teachers as one of the basic elements of learning and teaching. It has been right in the center of the teaching/learning process. Thus, an effective and efficient memory is of paramount importance for students as memory techniques can facilitate and improve the teaching/learning process. In the present paper the authors suggest some strategies and techniques that will undoubtedly go a long way in helping learners improve their memory in terms of encoding, storing and retrieving information.